Septic Cavernous Sinus Thrombosis Secondary to Acute Bacterial Sinusitis: A Retrospective Study of Seven Cases. Issue 1 (January 2015) - Lizé, Franklin; Verillaud, Benjamin; Vironneau, Pierre; Blancal, Jean-Philippe; Guichard, Jean-Pierre; Kania, Romain; Herman, Philippe
Background: Septic cavernous sinus thrombosis (SCST) is a rare but severe complication of acute bacterial sinusitis. Evaluations of advances in imaging techniques as well as in medical and surgical treatment are hampered by the lack of recent studies. Objective: We aim to report our experience in the management of SCST in patients with acute bacterial sphenoid sinusitis over the past 10 years and to discuss the initial work-up and treatment strategies. Methods: We performed a retrospective study of patients admitted for SCST related to acute sinusitis at a tertiary care center between 2003 and 2013. Clinical charts were reviewed for demographics, clinical presentations, imaging and microbiologic findings, medical and surgical treatments, and outcomes. Results: Seven patients were treated for SCST. Sphenoid sinus was involved in all cases. The most frequent presenting signs included headache (100%), cranial nerve impairment (86%), fever (71%), and orbital symptoms (71%). Diagnosis was confirmed by a cerebral contrast-enhanced CT scan in all cases. Four patients (57%) had an additional intracranial complication. The average time between clinical onset and diagnosis was 13.7 days. All patients were treated by high-dose i.v. antibiotics, anticoagulation therapy, and surgical endoscopic drainage of the infected sinuses. This treatment strategy resulted in a mortality rate of 0%, but four out of the seven patients developed transient or permanent neurologic deficits, including one with permanent unilateral visual loss. Conclusion: The combination of high-dose i.v. antibiotics, anticoagulation therapy, and endoscopic drainage of the infected paranasal sinus is an effective strategy for the treatment of SCST, but long-term sequelae remain frequent.